Integrative Learning from the Perspective of Hadith: Islamic Values, Ethics, and the Development of Science and Technology - M Thoharun; Muhid (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
Integrating the concept of Islamic Religious Education into the realities of modern life is a crucial area of study. This article aims to examine traditions concerning the relationship between Islamic values, ethics, and the development of science and technology. The research employs a literature-based approach, analyzing traditions related to integrative learning from the perspective of hadith. Integrative learning refers to an educational approach that connects various disciplines into a unified theme or combines one field of knowledge with others in a coherent and comprehensive manner. From the perspective of hadith, this model of learning is not only relevant but also deeply rooted in Islamic teachings. The hadiths examined in this study indicate that Islam promotes holistic models of education that emphasize harmonious relationships between teachers and students, interdisciplinary integration, and the continuity between classical and modern sciences. This demonstrates that Islam is not conservative but rather open and responsive to advancements in general science and technology. Through this approach, integrative learning based on hadith is expected to nurture insan kamil individuals who are intellectually capable, morally upright, spiritually grounded, and able to contribute meaningfully to society.